Phylogenetic Distribution and Prevalence of Genes Encoding Class I Integrons and CTX-M-15 Extended-Spectrum β-Lactamases in Escherichia coli Isolates from Healthy Humans in Chandigarh, India - Dureja, Chetna (PLoS One, 2014)
Escherichia coli is generally considered as a commensal inhabitant of gastrointestinal tract of humans and animals. The aim of this study was to gain insight on the distribution of phylotypes and presence of genes encoding integrons, extended β-lactamases and resistance to other antimicrobials in the commensal E. coli isolates from healthy adults in Chandigarh, India. PCR and DNA sequencing were used for phylogenetic classification, detections of integrase genes, gene cassettes within the integron and extended β-lactamases. The genetic structure of E. coli revealed a non-uniform distribution of isolates among the seven phylogenetic groups with significant representation of group A. Integron-encoded integrases were detected in 25 isolates with class 1 integron-encoded intI1 integrase being in the majority (22 isolates). The gene cassettes identified were those for trimethoprim, streptomycin, spectinomycin and streptothricin. The dfrA12-orfF-aadA2 was the most commonly found gene cassette in intI1 positive isolates. Phenotypic assay for screening the potential ESBL producers suggested 16 isolates to be ESBL producers. PCR detection using gene-specific primers showed that 15 out of these 16 ESBL-producing E. coli harboured the bla (CTX-M-15) gene. Furthermore, molecular studies helped in characterizing the genes responsible for tetracycline, chloramphenicol and sulphonamides resistance. Collectively, our study outlines the intra-species phylogenetic structure and highlights the prevalence of class 1 integron and bla (CTX-M-15) in commensal E. coli isolates of healthy adults in Chandigarh, India. Our findings further reinforce the relevance of commensal E. coli strains on the growing burden of antimicrobial resistance.